Literasi Keuangan Syariah dalam Minat Masyarakat Menggunakan Bank Syariah di Kecamatan Keruak Kabupaten Lombok Timur: Sharia Financial Literacy in Community Interest in Using Sharia Banks in Keruak District, East Lombok Regency - Eni Arnika (Lembaga Pendidikan Al-Gafari, 2026)
Islamic financial institutions are increasingly providing financial services and products based on Islamic law, and their growth is rapid. This study aims to answer the formulated problem, namely to identify how Islamic financial literacy influences public interest in using Islamic banks in Burau District, East Luwu Regency. This study uses quantitative methods. The data collection technique in this study was through the distribution of online questionnaires to respondents. The respondents referred to in this study were residents of Keruak District, East Lombok Regency, which has been limited by the author to people aged between 20 and 40 years. The population used in this study is the residents of Keruak District, East Lombok Regency. In this study, the author only used the community, because in this age range, they already have ID cards and are categorized as adults, who certainly already have knowledge about money management and this age range has the most interaction with financial issues. The analysis used in this study was a simple linear analysis using SPSS statistics software. The methods used were classical assumption testing, simple linear analysis, hypothesis testing, and coefficient of determination testing. The results of data analysis indicate that Islamic financial literacy influences public interest. The independent variable exerts a 39.5% influence, while other variables outside the study contribute 60.5%.